1991
DOI: 10.1111/j.1475-097x.1991.tb00650.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Doppler ankle pressures and skin perfusion pressure in subjects with and without diabetes

Abstract: Doppler ankle pressure measurements may be misleading in some patients because medial calcification has made the arteries of the leg incompressible. This problem is especially common in diabetics. Medical calcification that is not severe enough to make an artery clinically incompressible may cause an increased stiffness of the arterial wall that will limit the accuracy of Doppler ankle pressure measurements. A comparison of skin perfusion pressure, using an isotope technique, and Doppler ankle pressures was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…There are conflicting reports about skin capillary blood flow in the diabetic foot. Some studies have reported the absence of alterations in capillary blood circulation in neuropathic diabetics [18,19], while others observed a marked reduction in capillary blood perfusion in diabetic patients with or without peripheral arterial disease [20][21][22][23]. This suggests the presence of microangiopathy of the capillaries in diabetic patients with foot ulcer but does not confer any typical characteristics to patients with neuropathy alone or with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 83%
“…There are conflicting reports about skin capillary blood flow in the diabetic foot. Some studies have reported the absence of alterations in capillary blood circulation in neuropathic diabetics [18,19], while others observed a marked reduction in capillary blood perfusion in diabetic patients with or without peripheral arterial disease [20][21][22][23]. This suggests the presence of microangiopathy of the capillaries in diabetic patients with foot ulcer but does not confer any typical characteristics to patients with neuropathy alone or with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 83%
“…Very interestingly, this finding was independent of the presence of diabetes mellitus and renal insufficiency, factors known to be associated with both falsely high ABI values and risk of amputation. 2,4,12,20,21 A link between high ABI and poor outcome was found also in the Strong Heart Study, 17,18 which investigated a population with a high prevalence of diabetes mellitus. By contrast, results from the Atherosclerotic Risk in Communities Study 22 indicate that in general population with a low prevalence of PAD, those with a high ABI (Ͼ 1.3) do not suffer greater cardiovascular event rates than those with a normal ABI (0.9-1.3).…”
Section: Discussionmentioning
confidence: 99%
“…1 The relation of low ankle pressure to major amputation is lost among patients with ischemic foot lesion. 1 This is in part due to the fact that patients with CLI and ischemic lesions often have diabetes mellitus and are older, 3 factors known to cause medial arterial calcification (MAC), 11,12 which reduces the arterial compressibility and, thus, impairs the reliability of ankle pressure measurement. In these patients, alternative tests are needed to estimate the degree of circulatory impairment and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Low ABI measurements (< 0.90) have been studied as a marker of atherosclerotic peripheral arterial disease (PAD) for over 40 years [1]. PAD is commonly assessed by the measurement of ABI [2].…”
Section: Introductionmentioning
confidence: 99%